Pulse crop diseases in the Pacific Northwest. Issue 2 (24th May 2016) - Chen, Weidong
Abstract : This article provides a brief overview on some of the important diseases of pulse crops that farmers face in the Pacific Northwest. Some of the disease features are common among all pulse production areas, and some are peculiar to this particular region. Earn 1 CEU in Integrated Pest Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/763 .